2020
DOI: 10.1055/a-1244-1859
|View full text |Cite
|
Sign up to set email alerts
|

Trainee participation during screening colonoscopy does not affect ADR at subsequent surveillance, but may result in early follow-up

Abstract: Background and study aims Training future endoscopists is essential to meet rising demands for screening and surveillance colonoscopies. Studies have shown conflicting results regarding the influence of trainees on adenoma detection rates (ADR). It is unclear whether trainee participation during screening adversely affects ADR at subsequent surveillance and whether it alters surveillance recommendations. Patients and methods A retrospective analysis of average-risk screening colonoscopies and surveil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Seventeen articles with 18 datasets 8,9,19–33 (the study by Chalifoux et al 22 . contained two sets of data) regarding the association between fellow/trainee involvement and the detection rate of adenoma were included for meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Seventeen articles with 18 datasets 8,9,19–33 (the study by Chalifoux et al 22 . contained two sets of data) regarding the association between fellow/trainee involvement and the detection rate of adenoma were included for meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
“…There were 13 studies 8,19–27,29–31 comprising 14 datasets (the study by Chalifoux et al 22 . contained two sets of data) for investigating the association between fellow involvement and the detection rate of advanced adenoma.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, colonoscopy experience was not significantly associated with missed lesions. Previous studies have indicated that trainee participation in screening colonoscopy does not affect the ADR [ 30 , 31 ]; therefore, the same could be applied to missed lesion detection rates. Furthermore, an attending endoscopist should always perform follow up when trainees perform colonoscopy at our institution.…”
Section: Discussionmentioning
confidence: 99%